Deletion of both p62 and Nrf2 spontaneously results in the development of nonalcoholic steatohepatitis - Mizokami, Yuji; Tokushige, Katsutoshi; Ariizumi, Shun-ichi; Ishii, Tetsuro; Yanagawa, Toru; Ishige, Kazunori; Shoda, Junichi; Yamagata, Kenji; Warabi, Eiji; Akiyama, Kentaro; Kose, Katsumi; Yamamoto, Masakazu; et al. (Experimental Animals, 2018)
Nonalcoholic steatohepatitis (NASH) is one of the leading causes of chronic liver disease worldwide. However, details of pathogenetic mechanisms remain unknown. Deletion of both p62/Sqstm1 and Nrf2 genes spontaneously led to the development of NASH in mice fed a normal chow and was associated with liver tumorigenesis. The pathogenetic mechanism (s) underlying the NASH development was investigated in p62:Nrf2 double-knockout (DKO) mice. DKO mice showed massive hepatomegaly and steatohepatitis with fat accumulation and had hyperphagia-induced obesity coupled with insulin resistance and adipokine imbalance. They also showed dysbiosis associated with an increased proportion of gram-negative bacteria species and an increased lipopolysaccharide (LPS) level in feces. Intestinal permeability was elevated in association with both epithelial damage and decreased expression levels of tight junction protein zona occludens-1, and thereby LPS levels were increased in serum. For Kupffer cells, the foreign body phagocytic capacity was decreased in magnetic resonance imaging, and the proportion of M1 cells was increased in DKO mice. In vitro experiments showed that the inflammatory response was accelerated in the p62:Nrf2 double-deficient Kupffer cells when challenged with a low dose of LPS. Diet restriction improved the hepatic conditions of NASH in association with improved dysbiosis and decreased LPS levels. The results suggest that in DKO mice, activation of innate immunity by excessive LPS flux from the intestines, occurring both within and outside the liver, is central to the development of hepatic damage in the form of NASH.